Description Of Relationship Between Students Interests And Attitudes In Physical Subject In Indonesia - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Sumaryanti Sumaryanti; Rahmat Perdana; Susbiyanto Susbiyanto (Journal of Educational Science and Technology (EST), 2019)
The purpose of this study is to find out how attitudes and interests of students and analyze the relationship between attitudes and student interest in high school physics subjects in Jambi Province. This type of research is quantitative which uses survey research design as a research procedure. This study involved 463 high school students in Jambi Province. The instrument used was a questionnaire with data analysis techniques namely descriptive statistics and inferential statistics. The results of the dominant student attitude indicators discussed in this paper are attitude indicators towards good research in physics with a percentage of 58.5% with a total of 271 students. The results of indicators of dominant interest are indicators of learning attention with categories good a percentage of 74.3% with total 344 students. The results of the analysis of the relationship between attitudes and interests of students towards high school physics subjects in Jambi Province showed r value 0.725 and positive. Therefore it is said that the attitudes and interests of high school students in Indonesia in physics subjects are high.